Stress and Health Understanding the Effects and Examining Interventions - Taylor, Alyx (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Acute stressful experiences or high levels of chronic stress are risk factors for mental and physical disorders. Insights into the effects of posttraumatic stress disorder and other stress-related disorders experienced by war veterans, refugees, and immigrants are presented. This volume also presents examinations of the pathological effects of stress that may disrupt the normal relationships between individuals and their families. The health of individuals and their children may be enhanced by interventions to help them manage the effects of stressful life experiences and environments. Innovative and effective interventions are examined and their applications are recommended.